Evidence for the release of long‐term tectonic strain stored in continental interiors through intraplate earthquakes. Issue 13 (4th July 2016) - Craig, T. J.; Calais, E.; Fleitout, L.; Bollinger, L.; Scotti, O.
Abstract: The occurrence of large earthquakes in stable continental interiors challenges the applicability of the classical steady state "seismic cycle" model to such regions. Here we shed new light onto this issue using as a case study the cluster of large reverse faulting earthquakes that occurred in Fennoscandia at 11–9 ka, triggered by the removal of the ice load during the final phase of regional deglaciation. We show that these reverse‐faulting earthquakes occurred at a time when the horizontal strain rate field was extensional, which implies that these events did not release horizontal strain that was building up at the time but compressional strain that had been accumulated and stored elastically in the lithosphere over timescales similar to or longer than a glacial cycle. We argue that the tectonically stable continental lithosphere can store elastic strain on long timescales, the release of which may be triggered by rapid, local transient stress changes caused by surface mass redistribution, resulting in the occurrence of intermittent intraplate earthquakes. Key Points: Compressional end‐glacial earthquakes in Fennoscandia occurred in a setting where the contemporaneous horizontal strain rate was extensional End‐glacial earthquakes therefore tapped into tectonically derived strain accumulated and stored over a long timescale Seismic hazard in intraplate settings is influenced by nontectonic transients and may be more broadly distributed than commonly thought